Race and Public Policy in Maine: Past, Present, and Future - Myall, James (Maine Policy Review, 2020)
Maine’s bicentennial year is an appropriate moment to reflect on the historical legacy of public policy in Maine. In particular, the impact of historic policy decisions on people of color in the state is widely overlooked, perhaps because of Maine’s historical whiteness. This piece will show that, like the rest of the United States, Maine has a history of state-sanctioned discrimination, the consequences of which resonate today. Policymakers need to understand the harmful legacy of racist public policy in Maine if they are to avoid perpetuating those inequalities. Further, this piece will argue that it is not enough for lawmakers to avoid explicit or intentional racism in public policy, but that the state needs to be actively antiracist, with policies that intentionally work to improve the lives of people of color and correct historic wrongs.